Ketersediaan Zat Gizi Siswi Di Yayasan Pondok Pesantren Nurul Hakim Kediri Kabupaten Lombok Barat - Lale Rukmin; Luh Suranadi (Jurnal Gizi Prima (Prime Nutrition Journal), 2019)
Background : Riskesdas in 2013 showed that nationally  the prevalence of underweight in adolescents aged 13-15 years was 11.1%  (3.3%  thin and 7.8% very thin) and adolescents aged 16-18 years amounted to 9, 4% (1.9% thin and 7.5% very thin). NTB was the second of  the prevalence of underweight  in indonesia for age group 13-15 years and number  fourth for age group 16-18 years. So that needs to giving a good nutritions based on the average standard of adequacy of the recommended nutrients is the purpose of organizing food to maintain the boarders’s nutritional status. Objective : to describe the availability of energy and protein nutrients for students who  living in Yayasan Pondok Pesantren Nurul Hakim Kediri.  Methods : This study used a descriptive observational. The object of research is  foods that will be processed for 7 days, from 2nd to 8th February  2015. The data  of general overview of the location and identity of the students collected by secondary data searches in the administration of the school. The data of the implementation food and the availability of energy and protein nutrients collected by observation, weighing, conversion and analysis of oil absorption of nutrients by using DKBM and Nutrisurvey. All data were processed by descriptive method. Result : The average availability of energy and protein is still less than the standard  which  energy  64.1% and protein 54.0% of the RDA. This is due to the lack of use of a food that contains high-energy and high-protein, the use of a food that is not diverse, does not qualify balanced nutrition as well as the limited funds available. Conclusions: The availability of energy and protein nutrients in Nurul Hakim boarding school in Kediri west Lombok is less than the RDA.